THE INTERSECTION OF PHILOSOPHY OF SCIENCE AND CHRISTIAN RELIGIOUS EDUCATION: IMPLICATIONS FOR PRACTICAL VALUE - Solomon Giftman Sagala; Abdon Amtiran; Dyulius Thomas Bilo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research examines the practical implications of integrating ethical values, spirituality and philosophical principles in Christian religious education. Through the perspective of philosophy of science, especially in relation to values and morals, this research assesses how Christian religious education can respond to the challenges of globalization and technological development, while avoiding mystical teachings and religious manipulation. The research uses a qualitative method. Analysis was conducted through case study studies supported by literature references to produce a holistic understanding of the integration of philosophy of science and Christian religious education. The results revealed that the interaction between the philosophical foundation of scientific inquiry and the transcendent moral, ethical, and spiritual dimensions has great potential to enhance the practical relevance, social impact, and holistic resonance of Christian religious education. A deep integration of the empirical domain and spiritual values can bridge the gap between scientific knowledge and the values of human life. This approach opens new avenues for the development of educational practices that are attuned to the moral and intellectual needs of a global society. Christian religious education needs to maintain its relevance in the modern era by balancing religious values, philosophy and science. Moral guidance from the Bible provides a key foundation for creating meaningful social impact and building a morally and intellectually balanced society. This integrative perspective brings synergy that enriches the empirical and experiential realms, while empowering individuals and communities holistically.